Small Trafficking Inhibitor Retro-2 Disrupts the Microtubule-Dependent Trafficking of Autophagic Vacuoles - Nicolas, Valérie; Lievin-Le Moal, Vanessa (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is a catabolic recycling process by which a cell degrades its own constituents to contribute to cell homeostasis or survival. We report that the small trafficking inhibitor Retro-2 impairs microtubule-dependent vacuolar trafficking in autophagy. Retro-2 induced autophagy and promoted the dramatic cytoplasmic accumulation of large autophagosomes accompanied by the absence of autolysosome formation. In addition, Retro-2 abolished the spreading of autophagosomes within the cytoplasm of nutrient-starved cells. We show that these effects arise from hitherto unsuspected disassembly activity of the small molecule on the cellular microtubule network, which is known to act as a key regulator of vacuolar trafficking of the autophagy pathway.